EFFECT OF LIMB WEIGHT TRAINING ON SOME KINEMATIC VARIABLES LONG-RANGE SHOOTING IN YOUTH BASKETBALL (UNDER 16 YEARS OLD) - Hassan, Ghazwan Abdullateef (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Importance of this research lies in demonstrating the impact of these exercises on developing the mechanical aspects of long-range shooting skills among young basketball players. It also highlights the training method of limb weight training and its effect on certain kinematic variables related to long-range basketball shooting. This contributes to raising the level of skill performance, improving shooting accuracy, and achieving better results in sports competitions, research problem was the weakness and inconsistency in long-range shooting accuracy, in addition to some mechanical variables affecting the movement during the skill's execution. Objectives. Research objective was to identify the effect of limb weight training on certain kinematic variables in long-range basketball shooting among young players (under 16 years old). Method. The experimental method was used, and the research sample was the Basra Governorate Education Directorate team for the 2025-2026 season. After implementing the exercises. Results. By observing Tables (3) and (4) of the pre- and post-tests for the control and experimental groups, it became clear that both groups improved their kinematic variables and long-range shooting accuracy (calculated as three points). This is attributed to the regularity of training in both groups and their use of targeted exercises that affect the physical aspect, which in turn affects skill performance, including endurance. Conclusion. The weight training exercises enhanced the physical aspects, kinematic variables, and accuracy of three-point shooting in basketball for youth players (under 16 years old).